2009
DOI: 10.5194/cp-5-571-2009
|View full text |Cite
|
Sign up to set email alerts
|

A few prospective ideas on climate reconstruction: from a statistical single proxy approach towards a multi-proxy and dynamical approach

Abstract: Abstract. Important progresses have been made in palaeoclimatological studies by using statistical methods. But they are in somewhere limited as they take the present as an absolute reference. This is particularly true for the modern analogue technique. The availability of mechanistic models to simulate the proxies measured in the sediment cores gives now the possibility to relax this constraint. In particular, vegetation models provide outputs comparable to pollen data (assuming that there is a relationship b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…Such approaches based on forward modelling have been increasingly used in recent years using Bayesian statistics (e.g. Guiot et al 1999Guiot et al , 2009Haslett et al 2006;Hatté et al 2009;Haslett & Challenor 2010) and it is expected that their importance and relevance will continue to increase with increasing computational resources and our understanding about the relationships between climate parameters and proxy responses.…”
Section: New Approaches To Climate Reconstruc-tionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such approaches based on forward modelling have been increasingly used in recent years using Bayesian statistics (e.g. Guiot et al 1999Guiot et al , 2009Haslett et al 2006;Hatté et al 2009;Haslett & Challenor 2010) and it is expected that their importance and relevance will continue to increase with increasing computational resources and our understanding about the relationships between climate parameters and proxy responses.…”
Section: New Approaches To Climate Reconstruc-tionmentioning
confidence: 99%
“…assemblage composition) of the proxy-indicator (e.g. Guiot et al 2000Guiot et al , 2009. For example, Guiot et al (2000) used a mechanistic model of vegetation expressed as a function of climate.…”
Section: New Approaches To Climate Reconstruc-tionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hatté et al (2009) showed that the use of d 13 C as an additional constraint considerably reduces the uncertainties of climatic reconstructions obtained from inverse modelling compared to using pollen alone. Guiot et al (2009) have indicated that inverse modelling could provide an elegant solution of combining multiple data types, including lake-levels, d…”
Section: Including Multiple Data Sourcesmentioning
confidence: 99%
“…"High resolution" proxy records (Hughes and Ammann 2009) offer information about inter-annual and slower internal climate variabilities which in principle could be constrained by a suitable DA scheme. As a result, several research groups have been actively working with the purpose of paving the way towards an eventual paleo-reanalysis (Hughes et al 2010;Guiot et al 2009;Brönnimann 2011).…”
Section: Introductionmentioning
confidence: 99%